The Function of Story Structure in Shaping the Social Meaning of the Legend of Si Kantan Island - Wiradi, Dedek; Riyanto, Edi Dwi; Afdholy, Nadya (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2025)
This Research on the folklore of the legend of the Origin of Si Kantan Island in Central Panai District, Labuhan Batu Regency has a high urgency because until now this legend is still very much believed and alive in the local community, but in-depth studies of its structure and social function are still minimal. Most of the previous studies highlighted other North Sumatran legends such as Lake Toba or compared several legends in general, so there is a gap in specific understanding of the peculiarities of the narrative structure and social function of Pulau Si Kantan as a local cultural heritage.This research uses a descriptive qualitative approach to describe the structure and social function of the legend. Data were collected through the stages of identification, classification, discussion, and reporting. The results found that the structure of this folklore consists of characterization, plot, setting, language style, theme, and mandate. Meanwhile, its social functions include entertainment, education, value inheritance, and identity formation. This finding confirms that the legend of Si Kantan Island is still a highly trusted oral literature and plays an important role in shaping the identity and values of the local community to this day.